Clear aligner effectiveness in first premolar extraction orthodontic cases: A systematic review of tooth movement predictability - Helly G. Patel; Ajay Kantilal Kubavat; Khyati V. Patel; Yash A. Kayastha; Shreya H. Patel (Journal of Oral Research and Review)
This review compares the predictability of tooth movements with clear aligners in first premolar extraction patients, examining factors influencing outcomes, the accuracy of predicted versus actual movements, and the effectiveness of aligners in managing space closure and alignment across multiple studies. A systematic review following Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines was conducted, covering the period from January 2008 to March 2023. Databases searched included EMBASE, Web of Science, ResearchGate, PubMed CENTRAL, Cochrane Library, Google Scholar, and grey literature sources. Three reviewers assessed identified articles, with quality assessment of in vivo studies using the ROBIN-I tool for bias. Ten articles met the inclusion criteria out of 257 initially identified. These encompassed various study types: one is comparative study, one is prospective study, two are observational studies, three are retrospective studies, three are case reports. Most of the included studies heavily focused on predictability of tooth movements through clear aligner among first premolar extraction cases. Sample sizes ranged from 1 to 31. The material used were clear aligners of Invisalign® and ClinChek software. This systematic review underscores the importance of carefully selecting orthodontic appliances based on individual patient needs and treatment goals. While Clear aligner (Invisalign)® offers advantages such as minimal visibility and some movement flexibility, its efficacy varies across different clinical scenarios. In cases requiring premolar extractions or extensive tooth movements, fixed appliances may provide superior control and predictability. Further research is needed to improve orthodontic treatment protocols.